Pengaruh Inflasi, PDB, Kurs, Produksi Kreatif Sektor Kerajinan (Kriya) Terhadap Nilai Ekspor Kerajinan (Kriya) Di Indonesia Periode 2020-2022 - Anwar Syarif Harahap; Sugianto Sugianto; Muhammad Ikhsan Harahap (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to analyze the influence of leadership style and motivation on employee performance at the Regional Secretariat Office of Gowa Regency. This study uses a random sampling technique with a questionnaire as a tool to measure the variables of leadership style, motivation and employee performance variables. The analytical method used to test the hypothesis is multiple linear regression analysis based on data from 99 respondents using the Slovin formula that has completed all the questions in the questionnaire. The test used to test the research instrument is in the form of a validity test and a reliability test. Hypothesis testing uses the simultaneous test (f) and partial test (t). The results showed that the leadership style (X1) and motivation (X2) variables simultaneously had a significant and positive effect on employee performance (Y) at the Gowa Regency Regional Secretariat Office. While partially for leadership style variables (X1) and motivation (X2) on employee performance (Y) obtained a significant effect, but motivational variables more dominant influence on employee performance at the Gowa Regency Regional Secretariat Office